2005
DOI: 10.1002/jssc.200500183
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic enantiomer resolution of N‐fluorenylmethoxycarbonyl α‐amino acids and their ester derivatives on polysaccharide‐derived chiral stationary phases

Abstract: The liquid chromatographic enantiomer separation of N-fluorenylmethoxycarbonyl (FMOC) protected alpha-amino acids and their ethyl ester derivatives was performed on polysaccharide-derived chiral stationary phases, Chiralcel OD, Chiralpak AD, and Chiralpak AS. In general, Chiralcel OD and Chiralpak AD showed good performance for resolution of N-FMOC alpha-amino acids and their ethyl esters, respectively. All investigated N-FMOC alpha-amino acid enantiomers were baseline separated on Chiralcel OD or Chiralpak AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
2
Order By: Relevance
“…Particularly, polysaccharide-derived CSPs have been widely and successfully used for separating a variety of enantiomer compounds [2][3][4] . Related to this study, we have been reported enantiomer separation of α-amino acids and/or esters as several aromatic moiety derivatives using these polysaccharide-derived CSPs [5][6][7][8] . In this study, we focused on nitrobenzoxadiazole (NBD) group which is a fluorescence active derivatizing group of α-amino acids esters, because NBD fluorescence detection may provide strong advantages of selectivity and sensitivity in enantiomer separation.…”
Section: Introductionmentioning
confidence: 89%
“…Particularly, polysaccharide-derived CSPs have been widely and successfully used for separating a variety of enantiomer compounds [2][3][4] . Related to this study, we have been reported enantiomer separation of α-amino acids and/or esters as several aromatic moiety derivatives using these polysaccharide-derived CSPs [5][6][7][8] . In this study, we focused on nitrobenzoxadiazole (NBD) group which is a fluorescence active derivatizing group of α-amino acids esters, because NBD fluorescence detection may provide strong advantages of selectivity and sensitivity in enantiomer separation.…”
Section: Introductionmentioning
confidence: 89%
“…효율적인 광학분리를 위해 의약품개발 에서 흔히 사용되는 amino group이 보호된 α-amino acid 나 이들 유도체들의 광학분리를 수행하였다 [1][2][3]. 특히 α-amino acid ester의 경우에는 benzophenone imine Schiff base나 9-anthraldimine으로 이들을 유도체화 한 후에, 여러 키랄 고정 상에서 광학분리하는 새로운 분석법도 발표하였다 [4][5][6].…”
Section: 서론unclassified
“…Similarly, the introduction of the fluorenylmethyloxycarbonyl group (Fmoc) might require additional protection of the serine hydroxyl group [13,14] which makes the preparation of serine analytes more complicated (Figure 1C). To our best knowledge, only a few studies dealing with enantiosepa-ration of serine esters were published [25][26][27][28][29], all focusing only on short alkyl (methyl or ethyl) esters. Moreover, chromatographic enantioseparations of serine esters were conducted under normal phase conditions requiring toxic non-polar solvents and often toxic trifluoroacetic acid as an additive, too.…”
Section: Introductionmentioning
confidence: 99%